Place-value and physical size converge in automatic processing of multi-digit numbers. - Feder, Ami; Cohen-Gutman, Sivan; Lozin, Mariya; Pinhas, Michal (Memory & Cognition, 2024)
Previous research has shown that multi-digit number processing is modulated by both place-value and physical size of the digits. By pitting place-value against physical size, the present study examined whether one of the attributes had a greater impact on the automatic processing of multi-digit numbers. In three experiments, participants were presented with two-digit number pairs that appeared in frames. They were instructed to select the larger frame while ignoring the numbers within the frames. Importantly, we manipulated the physical size of the digits (i.e., both decade/unit digits were physically larger) within the frames, the unit–decade compatibility (i.e., the relationship between the numerical values of both decade and unit digits was consistent or inconsistent), and the congruity between the numerical values of the decade digits and the frames' physical size (i.e., decade-value–frame-size congruity). In Experiment 1, where all pairs were unit–decade compatible, a decade-value–frame-size congruity effect emerged for pairs with physically larger decade, but not unit, digits. However, when adding unit–decade incompatible pairs (Experiments 2–3), in unit–decade compatible pairs, there was a decade-value–frame-size congruity effect regardless of the digits' physical size. In contrast, in unit–decade incompatible pairs, there was no decade-value–frame-size congruity effect, even when the physically larger digit (i.e., unit) contradicted the place-value information, presumably due to the cancellation of the opposing influences of the digits' physical sizes their place-values. Overall, these findings suggest that place-value and physical size are intertwined in the Hindu–Arabic numerical system and are processed as one.